Focal Cortical Dysplasia Type IIB and Human Papillomavirus - J. Gordon Millichap (Pediatric Neurology Briefs, 2013)
Researchers at Temple University School of Medicine, Philadelphia, PA tested the hypothesis that human papillomavirus type 16 oncoprotein E6 (HPV16 E6) is present in human focal cortical dysplasia type IIB (FCDIIB) specimens.